Knowledge and fulfillment of biosecurity standards in nurse personal. Almanzor Aguinaga National Hospital. Chiclayo 2002 - SOTO, VÍCTOR (2004)
Objectives: To determine knowledge and fulfilment of biosecurity standards in nurses and nurse technicians who work in high risk areas. Material and Methods: Transversal, prospective and descriptive study. Population included nurses and nurse technicians who work at Emergency, Intensive Care Unit (ICU), Intermediate Care Unit (UCEMIN), General Surgery, Surgical Center, Neonatology and Hemodialysis services at Chiclayo Almanzor Aguinaga National Hospital, EsSalud. The sample included 117 workers, sample obtained by systematic and probabilistic selection. Knowledge level was determined by questionnaire and fulfilment by observation guide levels. Results: ICU and Surgical Center’s nurses and nurse technicians had a high level of knowledge in biosecurity standards; fulfilment varied from high fulfilment at the Surgical Center and least at General Surgery and UCEMIN; there were several common mistakes, such as, bad use of gloves, low frequency of hand washing, eating foods in not allowed places and needle hooding. Conclusions: There is a high level of knowledge on biosecurity standards in nurses and nurse technicians but fulfilment of the standards was level 2 (30 to 60%) only.